PENGARUH FINANCIAL LITERACY, FINANCIAL TECHNOLOGY, DAN HERDING BEHAVIOR TERHADAP KEPUTUSAN INVESTASI DENGAN RISK PERCEPTION SEBAGAI VARIABEL MODERASI PADA MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS LAMPUNG - Indah Permata Sari; Ahmad Faisol; Fajrin Satria Dwi Kesumah; Mahatma Kufepaksi (Nusantara Hasana Journal, 2026)
This study aims to empirically examine the effect of financial literacy, financial technology, and herding behavior on investment decisions, with risk perception as a moderating variable on students of the Faculty of Economics and Business, University of Lampung. The phenomenon of increased participation of young investors in the Indonesian capital market, including in Lampung Province, is not balanced with adequate financial literacy and vulnerability to irrational investment behavior. This condition underlies the need for further exploration of the determinants of investment decisions among students. This study uses a quantitative approach with a survey method. Data collection was conducted by distributing questionnaires to 46 students of the Finance Management Study Program from the 2021-2023 batch, selected using purposive sampling. Data analysis used Moderated Regression Analysis with the help of SPSS version 25 software. The results of this study indicate that, partially, financial literacy, financial technology, and herding behavior do not significantly affect student investment decisions. Risk perception is also not proven to moderate the influence of these three independent variables on investment decisions. However, simultaneously, all variables in the model, including financial literacy, financial technology, herding behavior, risk perception, and interactions between variables, significantly affect investment decisions. The Adjusted R² value of 46.9% indicates that the model is able to explain 46.9% of the variation in student investment decisions, while the remaining 53.1% is explained by factors other than those included in this research model. The results of this study show a gap between knowledge and action among students and confirm that investment decisions are a complex phenomenon influenced by the simultaneous interaction of various factors. This study provides a theoretical contribution to the development of Behavioral Finance Theory and practical implications for universities, regulators, and students in designing financial education programs that are more applicable and responsive to the dynamics of digital investment.